An Extraordinary Case of Maxillofacial Trauma: Injury by Harpoon Shot - Can Öncül, Enver; Apaydın, Can; Olgun, Yüksel (ENT Updates, 2022)
This case report presents a 24-year-old patient who accidentally received maxillofacial trauma with a speargun. One of the harpoons on the right and the other on the left had penetrated the submandibular region, and the floor of the mouth created lacerations on both sides of the tongue and extended into the nasal cavity by penetrating the hard palate bilaterally. In the maxillofacial computed tomography of the patient, the tip of the harpoon on the right ended in the right nasal cavity; however, it was seen that the tip of the speargun on the left side penetrated the frontal sinus on the left side. Both orbits and intracranial areas were regular. The patient was taken to an emergency operation. Tracheotomy was performed under local anesthesia to ensure airway safety. The harpoon on the left was removed from the body in the direction of the entrance with the help of forceps. While the harpoon on the right was removed in the direction of the entrance, the harpoon was removed by exploring the submandibular region due to the hook opening at the mouth’s floor. The patient, who had no complications in the postoperative follow-up, was discharged on the ninth postoperative day.